Considerations Regarding the Optically Transparent Rigid Model for PIV Investigations. A Case Study. Part 2: Notes on the Failure of the Model. (January 2016) - Giurgea, Corina; Bode, Florin; Nascutiu, Lucian; Dudescu, Cristian
Abstract: The transparent model that had been designed and manufactured as presented in the First Part of this paper was tested by the authors in a PIV investigation of the steady flow through a bifurcation. The outcomes of the first measurement campaign of their PIV investigation were reported by the authors in a previous paper. At the end of that measurement campaign it was found necessary to cut a few centimeters from the front side of the model that was exposed to the laser sheet because of burns that were observed in the measuring plane of the model. The changes in the appearance of the burned zone impeded the acquisition of the appropriate quality images for the PIV analysis. During a subsequent campaign the model failed because of a rapid evolution of a crack. Based on several results obtained by using qualitative methods (photo elasticity and thermography) and theirs correlation with information found in literature, the present paper aims to find answers to some legitimate questions that have arisen after the failure of the transparent model, questions regarding the causes of this incident.